Assessment of the stability of mercury concentrations in municipal waste using data science tools - Jędrusiak, Radosław; Chuchro, Monika; Bielowicz, Barbara; Gielar, Agnieszka (Geology, Geophysics and Environment, 2023)
Mercury and its compounds are among the most dangerous and toxic substances in the environment. As part of the study, several exploratory analyses and statistical tests were conducted to demonstrate how low and stable mercury content is in municipal waste. A statistical analysis of the mercury content in waste (waste codes 19 12 12 and 20 03 01) was carried out using advanced IT tools. Based on 32 results for each waste, the maximum mercury concentration was 0.062 mg/kg dry weight (EWC code 19 12 12) and 0.052 mg/kg dry weight (EWC code 20 03 01). The analysis, data inference, and modeling were performed according to the CRISP-dm methodology. The results obtained were compared with the maximum allowable mercury concentrations for agricultural soils (2 mg/kg dry weight) and the provisions of the Minamata Convention (1 mg/kg). The average, median, and maximum observed mercury concentrations in waste are significantly lower than the assumed levels of 2 mg/kg (permissible concentrations for II-1 soils) and 1 mg/kg (Minamata Convention). The stability of mercury content in waste was examined. Descriptive statistics, statistical tests, and regression modeling were used. The tests and analyses performed showed an insignificant variation in the mercury content of the wastes with codes 19 12 12 and 20 03 01. No trend or seasonality was observed. The analyses and tests performed confirmed that the data are stable, and the values are low.